2006
DOI: 10.1094/cm-2006-0227-02-rv
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Effects of Row Spacing on Weed Management in Corn and Soybean

Abstract: The adoption of narrow row spacings (rows less than 30 inches in width) in soybeans and corn has primarily been driven by the potential for higher yields in narrow‐ compared to wide‐row production systems. In addition to the potential yield advantages, these systems can have a significant impact on the incidence of weeds within a given agroecosystem and on the approach that producers might take for weed management. A review of row spacing experiments included in this review revealed that narrow row spacings ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 55 publications
4
37
1
Order By: Relevance
“…Also, soybean in 0.19– and 0.38‐m rows attained canopy closure (>95 light interception) at the R4 stage in 2010 and R5 stage in 2011, whereas soybean in 0.76‐m rows intercepted only 90% of the light at the R4 stage in 2010 and 87% of the light at the R5 and R6 stages in 2011. Increased light penetration into the canopy and slower time to canopy closure typically result in greater weed establishment in soybean (Bradley, 2006). Dalley et al (2004) also reported that soybean in 0.19‐ and 0.38‐m rows attained >98% canopy closure in 3 yr of a 4‐yr study, whereas soybean in 0.76‐m rows attained a maximum of only 84% in all 4 yr.…”
Section: Resultsmentioning
confidence: 99%
“…Also, soybean in 0.19– and 0.38‐m rows attained canopy closure (>95 light interception) at the R4 stage in 2010 and R5 stage in 2011, whereas soybean in 0.76‐m rows intercepted only 90% of the light at the R4 stage in 2010 and 87% of the light at the R5 and R6 stages in 2011. Increased light penetration into the canopy and slower time to canopy closure typically result in greater weed establishment in soybean (Bradley, 2006). Dalley et al (2004) also reported that soybean in 0.19‐ and 0.38‐m rows attained >98% canopy closure in 3 yr of a 4‐yr study, whereas soybean in 0.76‐m rows attained a maximum of only 84% in all 4 yr.…”
Section: Resultsmentioning
confidence: 99%
“…These weeds could be a problem when managing crop protection chemicals to avoid herbicide resistance, but were not yield limiting (Donald and Johnson, 2003). Late‐emerging weeds are common in wider crop row spacings (Yelverton and Coble, 1991; Nelson and Renner, 1999; Bradley, 2006). The solar corridor success depends on weed control, a requirement that has been a concern in other research (Pavlista et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In the central United States, planting full‐season corn in wide rows (76 cm) is usually sufficient for maximum yields compared to planting in narrow rows (<76 cm) (Lee, 2006), but limited research has evaluated ultra wide‐row corn (156 cm) using the solar corridor. Typically, row‐spacing studies recommend a narrow‐row spacing to close the canopy early, increase light interception and yields, reduce crop‐protection chemical use and production costs (Board et al, 1992; Nelson and Renner, 1999; Dalley et al, 2004; Bradley, 2006) and possibly avoid herbicide resistance. However, wide rows have been recommended to help manage diseases such as white mold [ Sclerotinia sclerotiorum (Lib.)…”
mentioning
confidence: 99%
“…Increasing maize population density reduced the competitiveness of weeds and increased maize yield . Narrow row and other planting configurations also provided benefits for weed and pest management, as well as for increased yield potential in maize, cotton and soybean . Research from Canada demonstrated that increased crop seeding rates contributed to weed suppression in several crops and was used by growers as a weed control tactic …”
Section: Adoption Of Selected Iwm Strategies To Manage Hr Weedsmentioning
confidence: 99%
“…89 Narrow row and other planting configurations also provided benefits for weed and pest management, as well as for increased yield potential in maize, cotton and soybean. 90,91 Research from Canada demonstrated that increased crop seeding rates contributed to weed suppression in several crops and was used by growers as a weed control tactic. 92,93 Planting configuration, specifically row width, also affects the crop canopy microclimate, which may change the crop morphology and resource utilization and improve weed management.…”
Section: Crop Population Density Planting Configuration and Plantingmentioning
confidence: 99%